Understanding how birds rebuild fat stores during migration: insights from an experimental study - Pedro M. Araújo (Nature Portfolio, 2019)
Abstract Mechanisms underlying fat accumulation for long-distance migration are not fully understood. This is especially relevant in the context of global change, as many migrants are dealing with changes in natural habitats and associated food sources and energy stores. The continental Black-tailed godwit Limosa limosa limosa is a long-distance migratory bird that has undergone a considerable dietary shift over the past few decades. Historically, godwits fed on an animal-based diet, but currently, during the non-breeding period godwits feed almost exclusively on rice seeds. The latter diet may allow building up of their fuel stores for migration by significantly increasing de novo lipogenesis (DNL) activity. Here, we performed an experiment to investigate lipid flux and the abundance of key enzymes involved in DNL in godwits, during fasting and refueling periods at the staging site, while feeding on rice seeds or fly larvae. Despite no significant differences found in enzymatic abundance (FASN, ME1, ACC and LPL) in stored fat, experimental godwits feeding on rice seeds presented high rates of DNL when compared to fly-larvae fed birds (~35 times more) and fasted godwits (no DNL activity). The increase of fractional DNL in godwits feeding on a carbohydrate-rich diet can potentially be enhanced by the fasting period that stimulates lipogenesis. Although requiring further testing, these recent findings provide new insights into the mechanisms of avian fat accumulation during a fasting and refueling cycle and associated responses to habitat and dietary changes in a migratory species.